Modeling irony a cognitive-pragmatic account - Lozano-Palacio, Inés (Figurative thought and language ;, 2022)
"This book adopts a broad cognitive-pragmatic perspective on irony which sees ironic meaning as the result of complex inferential activity arising from conflicting conceptual scenarios. This view of irony is the basis for an analytically productive integrative account capable of bridging gaps among disciplines and of recontextualizing and solving some controversies. Among the topics covered in its pages, readers will find an overview of previous linguistic and non-linguistic approaches. They will also find definitional and taxonomic criteria, an exhaustive exploration of the elements of the ironic act, and a study of their complex forms of interaction. The book also explores the relationship between irony, banter and sarcasm, and it studies how irony interacts with other figurative uses of language. Finally, the book spells out the conditions for "felicitous" irony and re-interprets traditional ironic types (e.g., Socratic, rhetoric, satiric, etc.), in the light of the unified approach it proposes"--